Notch of the Anterior Leaflet of the Tricuspid Valve with Severe Tricuspid Regurgitation. (March 2015) - Kuroda, Masataka; Ohta, Joe; Mita, Norikatsu; Miyoshi, Sohtaro; Kadoi, Yuji; Saito, Shigeru
<x xml:space="preserve">Abstract</x> Supplemental Digital Content is available in the text.